2006
DOI: 10.1007/s00192-006-0157-z
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical migration of an intrauterine contraceptive device complicated by bladder stone: a report of six cases

Abstract: Intrauterine contraceptive device is the most popular method of reversible contraception in developing countries due to its efficiency and low cost. However, this device is often inserted by paramedics of variable skills, and follow-up evaluations are irregular or absent which can be the source of major complications. The authors report six cases of intravesical migration of intrauterine contraceptive devices complicated by bladder stones. All the six cases were managed endoscopically with excellent outcome. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 7 publications
0
20
0
7
Order By: Relevance
“…In our case, there were only lower urinary tact symptoms. Some cases are asymptomatic (22). At radiological imaging, calcified intrauterine or intravesical devices can be misdiagnosed as a bladder stones (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, there were only lower urinary tact symptoms. Some cases are asymptomatic (22). At radiological imaging, calcified intrauterine or intravesical devices can be misdiagnosed as a bladder stones (5).…”
Section: Discussionmentioning
confidence: 99%
“…At radiological imaging, calcified intrauterine or intravesical devices can be misdiagnosed as a bladder stones (5). Migrated IUDs must be removed (22)(23) to avoid further complications.…”
Section: Discussionmentioning
confidence: 99%
“…Foreign bodies were reported to have been accidentally placed in female urethra during pro-cedures conducted to have a miscarriage or prevent pregnancy (5). Recently, it has been reported that various objects such as intrauterine devices, vaginal pessaries, artificial urinary sphincter, sling, non-absorbable materials used in Stamey procedures as well as surgical gauze entered into the bladder from adjacent organs (6,7). In rare cases, live objects such a leech can enter the bladder through the urethra (8).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of foreign body in the bladder may present with a little or no symptoms in the initial period, but as a complication of its presence in the bladder develops, irrtative LUTS become apparent and progressively worsen. [910111213] With infection and encrustation around it subsequently there is stone formation. Soon there is the development of both irritative and obstructive LUTS and hematuria[101415] from recurrent urinary tract infection and calculus irritation of the bladder mucosa.…”
Section: Discussionmentioning
confidence: 99%